Environmental Injustice and Electronic Waste in Ghana: Challenges and Recommendations - Njoku, Anuli; Agbalenyo, Martin; Laude, Janaya; Ajibola, Taiwo Folake; Attah, Mavis Asiwome; Sarko, Samuel Bruce (International Journal of Environmental Research and Public Health, 2023)
Electronic waste (e-waste) or discarded electronic devices that are unwanted, not working, or have reached their end of life pose significant threats to human and environmental health. This is a major concern in Africa, where the majority of e-waste is discarded. In the year 2021, an estimated 57.4 million metric tons of e-waste were generated worldwide. Globally, COVID-19 lockdowns have contributed to increased e-waste generation. Although Africa generates the least of this waste, the continent has been the dumping ground for e-waste from the developed world. The flow of hazardous waste from the prosperous ‘Global North’ to the impoverished ‘Global South’ is termed “toxic colonialism”. Agbogbloshie, Ghana, an e-waste hub where about 39% of e-waste was treated, was listed among the top 10 most polluted places in the world. The discard of e-waste in Ghana presents an issue of environmental injustice, defined as the disproportionate exposure of communities of color and low-income communities to pollution, its associated health and environmental effects, and the unequal environmental protection provided through policies. Despite the economic benefits of e-waste, many civilians (low-income earners, settlers, children, and people with minimal education) are exposed to negative health effects due to poverty, lack of education, and weak regulations. We critically examine the existing literature to gather empirical information on e-waste and environmental injustice. Comprehensive policies and regulations are needed to manage e-waste locally and globally.
Keywords: dept.pch; peer-reviewed

Environmental health disparities and maternal and child health: applying the life course approach - Wakeel, Fathima; Njoku, Anuli (Handbook of Social Sciences and Global Public Health, 2023)
Mounting evidence suggests that differential environmental exposures significantly contribute to a wide range of population health disparities. Adopting a life course approach to maternal and child health enables readers to uncover the mechanisms by which prenatal and early life environmental exposures potentially shape both short- and long-term physical and mental health outcomes. This chapter applies the life course approach to explore the adverse influences of environmental risk factors on maternal and child health. The following four case studies will be discussed: (1) the pervasive impacts of secondhand smoke; (2) the deleterious effects of lead exposure; (3) the development of asthma; and (4) the potential origins of autism spectrum disorder. The chapter also provides recommendations for programmatic and policy interventions to reduce the prevalence of four salient environmental hazards, including secondhand smoke, lead, air pollution, and pesticides, as well as proposed future directions in research regarding these exposures.
Keywords: Asthma; Autism spectrum disorder; Environmental health justice; Health equity; Lead exposure; Life course approach; Maternal and child health; Secondhand smoke exposure; dept.pch

Study plans and programs supporting geriatric dentistry teaching in Cuba: An update - Asanza, D.M.; Herrera, I.A.R.; Njoku, A.; Puig, A.C.R.; Mouloudj, F.; Capote, I.G.; Maupome, G. (Geriatric Dentistry in the Age of Digital Technology, 2023)
The aging population in the world constitutes one of the greatest challenges of the 21st century across social sectors; dental education is no exception. This review explored the status of geriatric dentistry teaching in Cuba and contrasted it with examples from international curricula and programs. Google Scholar, PubMed, Wiley, and Scielo databases were used to search for articles that address geriatric dentistry topics, focusing on undergraduate curricular issues and the management of postgraduate specialization. The findings highlight the need to update curricula and programs for dentistry studies in Cuba to improve the quality of dental care for the aging population. The evolution of training future Cuban graduates aims to meet the healthcare needs of older adults while preserving their quality of life. Additionally, the incorporation of new information and communication technologies has been observed during this process. © 2024, IGI Global. All rights reserved.
Keywords: dept.pch

Environment injustice and public health - Njoku, Anuli U.; Sampson, Natalie R. (Handbook of Social Sciences and Global Public Health, 2023)
Globally, air pollution accounts for approximately one in eight deaths, and diarrheal diseases account for one in nine child deaths annually. Lead exposure contributes to concerns of heart disease, stroke, and developmental intellectual disability. Further, across the world, nearly 23 million people are displaced by extreme weather events each year, which have been exacerbated by climate change and contribute to physical and mental health implications for entire communities. These and many other environmentally related experiences and their subsequent health outcomes are not experienced equally by race, ethnicity, or income, with Black, Brown, and Indigenous communities and low-income communities repeatedly experiencing the heaviest of burdens. Due to a variety of historic and contemporary policy and planning decisions, these patterns of environmental injustice persist on local, national, and global scales. In response, environmental justice (EJ) is a social movement, as well as a belief that people of all backgrounds deserve access to clean air and water and a healthy community in which to thrive. This chapter heavily focuses on the USA and its environmental health inequities, policies, and historic EJ movement. However, in our globalized society, EJ is a global issue that must be addressed as such by the field of public health.
Keywords: Cumulative impacts; Environmental justice; Health equity; Social determinants of health; Systemic racism; dept.pch

COVID-19, housing, and environmental injustice - Njoku, Anuli; Marcelin, Joseph (Hygiene, 2023)
Num Pages: 10
Keywords: dept.pch

Covid-19 and environmental racism - Njoku, Anuli; Marcelin, Joseph (Springer eBooks, 2023)
Keywords: dept.pch

Partnerships and Coalition Building for Advocacy - Breny, Jean M.; De Leon, Breanna; Schwartz, Elizabeth J. (Be the Change: Putting Health Advocacy, Policy, and Community Organization into Practice in Public Health Education, 2023)
The information and skills build to Chapter 10, where the work of a grassroots organization was investigated and how that work coincides with other advocacy and policy issues. Grassroots advocacy is a specific form of advocacy that starts from the roots (i.e., from the community itself) and grows upward from there. This is where the advocate deepens their knowledge about partnership building and collaboration and how it serves the profession to further the development of changes needed. Professional organizations and associations become important to the advocacy efforts at this level, and how to work together on the issues is shared.
Keywords: dept.pch

Language preferences and impact of labels on the lived experience of people who use heroin - Boeri, Miriam; Lamonica, Aukje K.; Chow, Clifton; Whalen, Thor (Drugs: Education, Prevention and Policy, 2023)
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/09687637.2023.2262097
Keywords: Stigma; attitudes; dept.pch; heroin; labels; language preferences; lived experience; mixed methods; peer-reviewed; replication studies

Systems and methods for solar-electric pump-out boat - Pascucilla, Michael A. (2023)
A solar electric pump-out boat for removing human waste. The pump-out boat may include a boat hull, wherein the boat hull may include a bow, a stern, and a self-draining sole disposed therein. The pump-out boat may further include a holding tank disposed within the hull underneath the self-draining sole for collecting waste. The pump-out boat may further include a console disposed approximately center of, and on a top surface of the self-draining sole. The pump-out boat may further include a solar panel for absorbing sunlight to convert into electrical power. The pump-out boat may further include a pump disposed within the console. The pump-out boat may further include a battery connected to a motor, the pump, and the solar panel, such that the solar panel charges the battery to provide the electrical power to operate the pump and the motor.
Keywords: dept.pch

Spaces to heal: providing the table and seats - Njoku, Anuli; Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Black, Indigenous, and People of Color (BIPOC) women faculty and administrators are breaking barriers, maintaining excellence, becoming award-winning scholars, and flourishing as experts in their fields. Still, they must survive while they thrive, grappling with insecurity, writer’s block, and imposter syndrome. Further examination prompts the realization that imposter syndrome may be a scapegoat for structural racism. Moreover, COVID-19 has created substantial health and financial tolls, fueled mental and emotional fatigue, and disrupted workplace productivity. These barriers caused by COVID-19 and structural racism inspire the courage to reassure, uplift, mentor, invite, and make collaborative spaces for BIPOC women to express feelings of vulnerability, unease, and, ultimately, hope. When seats are missing at the table, one can bring their own table and seats. In a field of often unforgiving critics, the authors provided underrepresented scholars the opportunity to promote authenticity and illuminate their voices. This chapter shares the authors’ reflections on being able to share the diverse and resilient perspectives of BIPOC women in academia.
Keywords: BIPOC women faculty; COVID-19; Imposter syndrome; Self-preservation; Sisterhood in the academy; dept.pch

Coping resources and self-care during COVID-19, police brutality, and social unrest - Njoku, Anuli (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
U.S. society has been gripped with dueling pandemics of racial and ethnic disparities in COVID-19 outcomes, highly publicized instances of police brutality against Black persons, and ensuing unrest to challenges these atrocities. In higher education, the rapid pivot response to COVID-19 with remote and virtual learning has also highlighted multiple levels of mental health trauma and disparities. There has also been vicarious trauma for Black women in academia who may have seen their family, friends, or loved ones reflected during increased media coverage of police brutality. This implores the need for effective strategies to mitigate these issues. This chapter discusses evidence-based strategies for Black women who navigate academia and teach during times of COVID-19 and social unrest. This chapter also proposes strategies for university leaders to consider alleviating cultural and racial gaps in the classroom or workplace and foster diversity and inclusion in academia.
Keywords: Academia; Black women; COVID-19; Higher education; Police brutality; Trauma; dept.pch

ACEing the Black Trauma of the COVID-19 Pandemic - Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
When I first took the adverse childhood experiences (ACEs) quiz, I was overcome with the enormity of Black trauma contained in those ten questions. The quiz reflected my own story, as well as those of Black students, women, and families—traumas that were magnified by the impact of three pandemics: COVID-19, economic inequities, and systemic racism. The definition of trauma as “emotional responses to disastrous life events” like COVID-19 can have both short- and long-term health consequences throughout one’s lifespan. The impact of COVID-19 as Black trauma in my family will reverberate long after society heals from the last three years and moves toward living with COVID-19 symbiotically. It is imperative to recognize ACEs and their perpetual trauma to implement successful trauma-informed practices to counteract and undo the damaging effects of COVID-19 on our collective lives.
Keywords: ACEs quiz; Adverse childhood experiences; COVID-19; Trauma-informed practices; dept.pch

It’s a win-win: faculty-mentored research with students of color - Njoku, Anuli; Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
In addition to fueling health disparities, the COVID-19 pandemic has exacerbated inequities among faculty of color. COVID-19 has also taken a dramatic toll on college students’ mental health, with evident racial disparities. Gender inequality in research productivity has also been revealed, with women submitting fewer papers compared to men. This pandemic has created an opportunity, of sorts, to promote academic and career success among women and students of color in academia. Research has shown that mentorship and research opportunities improve chances for success among students of color in higher education. Faculty members can also progress personally and professionally from such collaborations. Still, students of color are not equally given opportunities to collaborate with faculty on research. This chapter shares perspectives and strategies from Black women faculty and graduate students regarding faculty-student research to promote academic and career success among faculty and students of color in academia.
Keywords: COVID-19; Faculty-mentored research; Mentoring; Student research; Students of color; dept.pch

Giving Up Is Never an Option: Personal and Professional Development During COVID-19 - Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
COVID-19 brought me challenges and opportunities. I lost important people in this pandemic but also accomplished a lot. COVID-19 gave me a chance to soul search, grow, and develop. I blossomed into the woman I have always wanted to be but could not find. During it all, I was awarded my undergraduate degree, got accepted to a graduate program, received a new job, and bought my first car. With every blessing came a challenge, including health problems. Still, I persevered. Opportunities continue to present themselves and I seize them. Professional successes included publishing an article, presenting at a state public health conference, being featured in my university’s annual newsletter, and nailing my dream job! I got to “See Me!”, a woman of color coming from another country, accomplishing so much in a short span of time. This chapter details a true testimony and how giving up is not an option.
Keywords: COVID-19; Graduate students; Mental health; Resilience; dept.pch

Navigating academia during COVID-19: perspectives and strategies from BIPOC women - Njoku, Anuli; Evans, Marian (Springer International Publishing, 2023)
Keywords: BIPOC faculty; Covid-19; Gender and Education; dept.pch; narrative inquiry; professional development; trauma

Modeling predictors of medication waste reduction intention in Algeria: extending the theory of planned behavior - Mouloudj, Kamel; Njoku, Anuli; Asanza, Dachel Martínez; Bouarar, Ahmed Chemseddine; Evans, Marian A.; Mouloudj, Smail; Bouarar, Achouak (International Journal of Environmental Research and Public Health, 2023)
COVID-19 caused an increase in the demand for medications, which led to an increase in pharmaceutical waste and there is no doubt that this contributes to environmental pollution. Hence, it became necessary to search for how to protect and improve the environment by encouraging the behavior of medication waste reduction. Accordingly, this study aims to investigate the factors affecting intentions to reduce medication waste. Considering this, we develop an extended theory of planned behavior (TPB) framework by incorporating the constructs of moral obligation, environmental awareness, and medication waste risk perception. Using the convenience sampling method and based on a self-administered questionnaire, a total of 225 usable responses were collected in five Algerian cities. The results showed that positive attitudes (β = 0.316, p < 0.001), moral obligation (β = 0.291, p < 0.001), environmental awareness (β = 0.227, p < 0.001), perceived behavior control (PBC) (β = 0.151, p = 0.001), greater perceived risks (β = 0.127, p < 0.001), and subjective norm (β = 0.096, p < 0.05) significantly and positively influence the medication waste minimization intention. Furthermore, our analyses revealed that the extended TPB model explained 73.40% of the intention variance. In conclusion, we have explored the intentions, and there may be a gap between intent and actual behavior. Therefore, we recommend future studies to examine the factors affecting the actual behavior of medication waste reduction and to investigate environmental ethics and religious commitment as predictors of waste reduction intentions.
0 citations (Crossref) [2023-10-31] Number: 16
Keywords: Africa; dept.pch; environmental health; environmental pollution; medication ecotoxicity; medication waste; moral obligation; peer-reviewed; perceived risk; pharmaceutical waste; theory of planned behavior; unused medications

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
0 citations (Crossref) [2023-10-31]
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

Racial and Ethnic Disparities in Chronic Stress among Male Caregivers - Unson, Christine; Njoku, Anuli; Bernard, Stanley; Agbalenyo, Martin (International Journal of Environmental Research and Public Health, 2023)
Whereas research on caregiving is well documented, less is known about gender inequalities in caregiver stress, coping mechanisms, and health outcomes, all of which may vary by race, ethnicity, and socioeconomic status. This scoping review investigated racial and ethnic disparities using the Stress Process Model among male caregivers. Several databases were searched including Academic Search Premier, Medline Complete, APA PsycInfo, CINHAL, Google, ProQuest, and Web of Science. Included were peer-reviewed articles in English, published from 1990 to 2022. A total of nine articles fulfilled inclusion criteria. Most of the articles indicated that compared to White male caregivers, African American male caregivers provided more hours of care, assisted with more activities of daily living (ADLs) and instrumental activities of daily living (IADLs), and experienced more financial stress. In terms of coping style, one study found African American male caregivers, compared to White male caregivers, held negative religious beliefs. Another study showed that they were at a higher risk for stroke than their White counterparts. The search revealed a dearth of studies on racial disparities in stress, coping, and health outcomes among male caregivers. Further research is needed on the experiences and perspectives of male minority caregivers. © 2023 by the authors.
0 citations (Crossref) [2023-10-31]
Keywords: African American males; aging; caregiver burden; caregiving; coping; dept.pch; health and aging; health disparities; intersectionality; male caregiver; masculinity; older adults; peer-reviewed

"Go with the flow": a qualitative description of infant feeding experiences among women with hiv in the united states - Pagano-Therrien, J.; Griswold, M.K.; Amoah, R.K. (The Journal of the Association of Nurses in AIDS Care : JANAC, 2023)
ABSTRACT: Breastfeeding affords numerous health benefits to mothers and children, but for women with HIV in the United States, avoidance of breastfeeding is recommended. Evidence from low-income countries demonstrates low risk of HIV transmission during breastfeeding with antiretroviral therapy, and the World Health Organization recommends exclusive breastfeeding and shared decision making about infant feeding options in low-income and middle-income countries. In the United States, gaps in knowledge exist surrounding the experiences, beliefs, and feelings of women with HIV surrounding infant feeding decisions. Undergirded by a framework of person-centered care, this study describes the experiences, beliefs, and feelings of women with HIV in the United States surrounding recommendations for breastfeeding avoidance. Although no participants reported consideration of breastfeeding, multiple gaps were identified with implications for the clinical care and counseling of the mother-infant dyad. Copyright © 2023 Association of Nurses in AIDS Care.
1 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Factors influencing the adoption of digital health apps: an extended technology acceptance model (TAM) - Mouloudj, Kamel; Bouarar, Ahmed Chemseddine; Asanza, Dachel Martínez; Saadaoui, Linda; Mouloudj, Smail; Njoku, Anuli U.; Evans, Marian A.; Bouarar, Achouak (Integrating Digital Health Strategies for Effective Administration, 2023)
Mobile health apps have been widely considered in the healthcare sector as innovative channels to reach patients and their families. Accordingly, the aim of the chapter was to investigate factors that influence the customers' adoption of digital health apps in Algeria. The authors adopted an extende...
Keywords: dept.pch

Exploring What Influences Heterosexual College Men and the Practice of Safe Sex: The Power of Stigma and Community - Breny, J.M.; Joseph, M.; Robledo, D.; Rondeau, D.; D’Haity, W.; Mucha, J.; Zapata, P. (Journal of Community Health, 2023)
The college student population is among the highest risk group for contracting sexually transmitted infections (STIs) such as gonorrhea, chlamydia, and HIV. Safe sex practices, which are intended to mitigate risks associated with sexually transmitted infections, are often negated in the population of heterosexual college students. Historically, research on safe sex practices has shown that the burden of behavior change and the focus on educational efforts historically fall onto the female population. There is little published on how safe sex education for males impacts attitudes and behaviors towards safe sex practices. This community-based participatory research (CBPR) project explored heterosexual college male attitudes and behaviors about safe sex responsibilities with the goal of creating effective health promotion messages to increase safer sex. The research team comprised almost entirely of undergraduate male students, which strengthened the design and translation of results to practice. A mixed methods design was employed utilizing both focus groups and surveys as data collection (n=121). Results showed that young men are still prioritizing pregnancy prevention over disease contraction and/or testing, and relying on female partners to initiate safe sex. Implications for health promotion practice efforts on college campuses include: male-led peer education programming and support and messaging around screening and prevention of STIs. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
0 citations (Crossref) [2023-10-31]
Keywords: CBPR; College health promotion; Condom use; HIV prevention; Peer education programs; STI prevention; dept.pch; peer-reviewed

Creating a Narrative for Change: Health Promotion Students’ Perspectives on the Power of Photovoice Research - De Leon, Breanna; Mahama, Fatawu; Raymond, Ashley; Palmer, Cheryl A; Breny, Jean M. (Health Promotion Practice, 2023)
The use of Critical Race Theory, Photovoice, and Community-Based Participatory Research has helped uncover the root causes of issues such as systemic racism in the fields of public health and health promotion. Often, we see studies using traditional research methods to investigate potential causal factors of disparities in minoritized communities report only quantitative data. While these data are imperative for understanding the severity of disparities, quantitative-only approaches cannot address nor can they improve the critical root causes of these disparities. As a team of BIPOC graduate students in public health, we conducted a community-based participatory research project using Photovoice methodology to explore inequities in Black and Brown communities exacerbated during the COVID-19 pandemic. The participatory nature of this research revealed cumulative challenges across the social determinants of health in New Haven and Bridgeport, Connecticut. It allowed us to engage in local-level advocacy to promote health equity as our findings illuminated the need for community-led and community-engaged action. Health and racial inequities cannot be effectively addressed if public health research and programming do not collaborate with the community to build community capacity, empowerment, and trust. We describe our experiences doing community-based participatory research to investigate inequities and provide reflections on their value for public health students. As responses to health inequities and disparities become more politically polarized in the United States, it is critical for public health and health education students to use research methodologies that elevate communities that have been historically marginalized and neglected. Together, we can catalyze equitable change.
1 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Listen to the whispers before they become screams: addressing black maternal morbidity and mortality in the united states - Njoku, Anuli; Evans, Marian; Nimo-Sefah, Lillian; Bailey, Jonell (Healthcare, 2023)
Black women in the United States (U.S.) disproportionately experience adverse pregnancy outcomes, including maternal mortality, compared to women of other racial and ethnic groups. Historical legacies of institutionalized racism and bias in medicine compound this problem. The disproportionate impact of COVID-19 on communities of color may further worsen existing racial disparities in maternal morbidity and mortality. This paper discusses structural and social determinants of racial disparities with a focus on the Black maternal mortality crisis in the United States. We explore how structural racism contributes to a greater risk of adverse obstetric outcomes among Black women in the U.S. We also propose public health, healthcare systems, and community-engaged approaches to decrease racial disparities in maternal morbidity and mortality.
3 citations (Crossref) [2023-10-31] Number: 3
Keywords: COVID-19; black maternal mortality; dept.pch; health disparities; intersectionality; morbidity; peer-reviewed; pregnancy; race/ethnicity; racism; social determinants of health; weathering framework